Wireless Mesh Networks for IoT and Smart Cities: Technologies and Applications - Davoli, Luca; Ferrari, Gianluigi (IET telecommunications series ;, 2022)
Covering new developments and state-of-the-art research in Wireless Mesh Networks (WMNs), this edited book is a useful reference for ICT networking engineers, researchers, scientists, engineers, advanced students and lecturers in both academia and industry working on Wireless Communications and WMNs.